Preemptive acyclovir to prevent herpes simplex virus bronchopneumonitis in mechanically ventilated patients with herpes simplex virus oropharyngeal reactivation: An ancillary study of the preemptive treatment for herpesviridae trial. Issue 1 (3rd February 2022) - Troger, Antoine; Burrel, Sonia; Pineton de Chambrun, Marc; Schmidt, Matthieu; Bréchot, Nicolas; Bomme, Olivier; Hékimian, Guillaume; Combes, Alain; Boutolleau, David; Luyt, Charles-Edouard
Background: To evaluate the impact of preemptive acyclovir treatment on herpes simplex virus (HSV) bronchopneumonitis in mechanically ventilated patients with HSV oropharyngeal reactivation. Methods: Ancillary study of the Preemptive Treatment for Herpesviridae (PTH) clinical trial. Patients included in that trial from one centre (Pitié-Salpêtrière Hospital) and in whom at least one bronchoalveolar lavage (BAL) was performed for ventilator-associated pneumonia suspicion were included in the present study. Rate of HSV bronchopneumonitis, defined as clinical symptoms suggesting of pneumonia and presence of HSV in BAL fluid ≥10 5 copies of HSV/10 6 cells, were compared in patients who received either acyclovir or placebo. Results: Eighty-three patients were included; 40 having received preemptive acyclovir and 43 having received a placebo, without differences between groups at admission or at randomization. The number of patients who developed HSV bronchopneumonitis was lower among acyclovir-treated patients than among placebo-treated patients (40% vs. 72%, respectively, p = .003). Results were similar when restricted to patients without HSV detected in the lower respiratory tract at randomization (31% vs. 61%, respectively, p = .03). Conclusions: Preemptive acyclovir treatment in mechanically ventilated patients with HSV oropharyngeal reactivation reduces HSV bronchopneumonitis rate.